PELVIC EXENTERATION AND ITS REPERCUSSION ON FEMALE SEXUALITY - Silva, Aline Reis Oliveira da (2024)
Cancer is a public health problem in Brazil and worldwide. For women, cancers of the colon and rectum, cervix, ovary and body of the uterus are among the 10 most common. Treatment can include surgery, chemotherapy and/or radiotherapy. Among the surgical modalities, pelvic exenteration (PE) is a challenging procedure that can bring changes to sexuality. In order to contribute to a reflection on the subject, an integrative literature review was carried out with the aim of identifying the repercussions of this procedure on women's sexuality. The following databases were consulted: BVS, IBECS and MEDLINE, using the descriptors Pelvic Exenteration, Sexuality, Female and Psychology. 106 studies were found and six were selected. The articles deal with the physical, psychological and sexual repercussions of PE. Through the results, the discussion was divided into four categories, showing that PE brings changes in various areas of life, developing physical, psychological and sexual symptoms. The study achieved its aim and the results highlight the effects of this procedure on patients' lives. It is therefore important to provide comprehensive, multidisciplinary care before and after PE, in order to cover all needs during treatment.